Posthumanism for Sustainability: A Scoping Review - Dedeoğlu, Çağdaş; Zampaki, Nikoleta (Journal of Posthumanism, 2023)
The purpose study is to explore relationship between posthumanism and sustainability and contribute to interdisciplinary concept of posthuman sustainability. We conducted a scoping review of 45 peer-reviewed journal articles that met our inclusion criteria and employed co-occurrence analysis based on the clustering techniques of the VOSviewer. We identified five themes within the articles: post-humanism, post-anthropocentrism, post-dualism, post-Enlightenment, and post-technologism. Through our analysis, we found that posthumanism can offer insights into ecological issues and help promote alternative sustainable practices. We also identified three immediate concerns for post/humanities scholars: (1) fostering dialogue between critical humanist and posthumanist scholarship based on onto-epistemological plurality, (2) achieving conceptual clarity in the field, (3) advocating for meaningful engagement with indigenous worldviews in a multidimensional and multitemporal manner. By exploring the relationship between posthumanism and sustainability, we hope to expand our knowledge of the urgent ecological issues we face and contribute to interdisciplinary efforts to address them.